2013
DOI: 10.1007/s00595-013-0504-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the outcome of image-guided percutaneous drainage of intra-abdominal abscess after gastrointestinal surgery

Abstract: PurposeTo improve the selection of patients for percutaneous abscess drainage (PAD) to treat postoperative intra-abdominal abscess after gastrointestinal surgery, we investigated the factors predictive of outcome.MethodsOf 143 consecutive patients with symptomatic postoperative intra-abdominal abscess after a gastrointestinal tract resection, 104 who underwent image-guided PAD as the initial treatment were reviewed. We assessed the possible associations between successful PAD and patient-, abscess-, surgical-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Ultrasonogram was at par with CT scan for guidance of PCD, hence, it may be preferred being easily available, cheaper and without radiation exposure. PCD has a prime role in the treatment of post-operative collections with a success rate of 81%-85.6%, an observation echoed by our study where PCD had immense success [5][6][7]. PCD may be complicated by bleeding, hollow viscus perforation, migration etc.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Ultrasonogram was at par with CT scan for guidance of PCD, hence, it may be preferred being easily available, cheaper and without radiation exposure. PCD has a prime role in the treatment of post-operative collections with a success rate of 81%-85.6%, an observation echoed by our study where PCD had immense success [5][6][7]. PCD may be complicated by bleeding, hollow viscus perforation, migration etc.…”
Section: Discussionsupporting
confidence: 53%
“…The success rate of image guided PCD ranges widely from 70%-97% for single / late onset abscess and about 80% in cases of multiple/ early onset abscesses [5][6][7]. Large sized collections, multiple collections and CT guided aspirations have been found to result in higher success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Golfieri et al described that there is a general consensus among studies in the literature about PAD in conjunction with antibiotics as initial treatment for postoperative intra-abdominal abscesses [8]. In our previous study, we examined 104 patients with postoperative abscesses with and without anastomotic leakage who underwent image-guided PAD as the initial treatment [27]. A multivariable analysis showed that a shorter interval between surgery and onset and having multiple abscesses, but not the use of antibiotic therapy, were related to the failure of PAD.…”
Section: Discussionmentioning
confidence: 98%
“…Некоторые ав-торы предлагают агрессивную терапию с хирур-гическими повторными вмешательствами, в то время как другие рекомендуют консервативное лечение антибиотиками широкого спектра дейс-твия, полным парентеральным питанием и на-ружно-внутренним чрескожным дренированием. По данным Ercoli et al на основании анализа 99 пациентов с абдоминальными и забрюшинными абсцессами, связанными с высокими кишечными свищами, продемонстрирована эффективность ведения пациентов на чрескожных дренажах [12]. При этом у двух (13%) пациентов было полное разрешение свищей, у 10 (67%) пациентов слу-чился рецидив абсцессов, у троих (20%) паци-ентов технически не получилось провести чрес-кожный дренаж и были проведены открытые операции.…”
Section: Discussionunclassified